Strategi Pembelajaran Menggunakan Aplikasi Edmodo Dalam Pembelajaran Seni Tari Kelas X Jurusan TOI (Teknik Otomasi Industri) Di SMK SMTI Padang - Bunga Rahmadillah; Yuliasma Yuliasma (SENDRATASIK UNP, 2022)
This study aims to identify and describe the strategies used in learning dance using the Edmodo application in class X majoring in TOI at SMK SMTI Padang. This research is a type of qualitative research with a descriptive analysis approach. The resource person for this research was Ms Rafvita Asmil S.Pd. and class X students majoring in TOI at SMK SMTI Padang totalling 38 people using primary and secondary data types. Data collection techniques used in this study using literature study techniques, interviews, observation, and documentation. The data analysis technique in this study is to identify the data, classify the data, clarify the data, analyze the data and conclude the data. The results of this study are the Edmodo application which is a medium to carry out the learning process has weaknesses, so that cultural arts teachers have limitations in implementing dance learning strategies, this can be seen from the lack of enthusiasm of students in the learning process, lack of student response in the learning process, lack of appearing questions from the learning process by students, limited learning interactions.